Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Di Jabodetabek - Aminah Safitri; Rahel Meinita Wijayanti; Rissa Rahma Sari (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2023)
This study intends to analyze the influence of transformational leadership style, work motivation, work stress, and job satisfaction on employee performance in several companies in Jabodetabek. Sampling was carried out by distributing questionnaires to 100 respondents. The data was processed using SmartPLS 4.0 software and the Structural Equation Modeling (SEM) method to find out significant variables to employee performance (Y) in companies in Jabodetabek. The results of this study indicate that (1) transformational leadership style has a positive and significant effect on employee performance, (2) work motivation has a positive and significant effect on employee performance, (3) work stress has a negative and insignificant effect on employee performance, and (4) job satisfaction has a positive and significant impact on employee performance in companies in Jabodetabek. Keywords: Transformational Leadership, Work Motivation, Work Stress, Job Satisfaction, Employees Performance